Pelatihan Desain Grafis For Kids dengan Paint dalam Mendukung Kabupaten Labuhanbatu Layak Anak - Abdul Karim (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Graphic design for children has an important role in the overall development of a child. A well-designed product or environment can stimulate children's imagination, creativity and thinking abilities. Good design can also help children learn and interact with their environment in a positive way. This training uses the Paint application which is easy to use and suitable for beginners. The purpose of this training is to provide children with an understanding of graphic design so that they understand the meaning of the design itself and can utilize technology and encourage child-friendly district programs in Labuhanbatu. The results of this training will be so that children can understand and be able to utilize design as one of their skills. The results of this training will be so that children can make a standard design they want.